IMPROVING STUDENTS’ LEARNING OUTCOMES THROUGH IMPLEMENTATION OF PROJECT-BASED LEARNING INTEGRATED WITH LOCAL WISDOM - Sri Bintang Kusumawati; Yuni Ratnasari; Fitriyah Amaliyah (JURNAL PENA SAINS, 2025)
The success of achieving learning objectives is seen from student learning outcomes, seen from the knowledge aspect for the elements of the concept of science, and science, as well as attitudes and skills based on the elements of science and science process skills. Teachers who are less creative and innovative in implementing learning models that are suitable for students will affect student learning outcomes. This causes a monotonous, boring, and uninteresting learning atmosphere for students, so that students' science learning outcomes are still relatively low from the predetermined KKTP value. In addition, in this era of increasingly rapid technology and globalization, it can cause a shift in culture and local wisdom for the younger generation. Therefore, this study aims to determine the increase in science learning outcomes by using the Project-Based Learning model containing local wisdom at SD N Ngepungrojo 01 Pati. The Project-Based Learning model, containing local wisdom, is a learning model that uses projects by integrating local wisdom. The stages of the Project-Based Learning model are divided into six stages. The research method that will be used in this study is pre-experimental with a one-group pretest-posttest design. Data analysis techniques consist of initial data analysis using validity tests and normality tests, and research data analysis using the Paired Sample T-Test and N-Gain test.